2017
DOI: 10.1371/journal.pone.0180908
|View full text |Cite
|
Sign up to set email alerts
|

BEASTling: A software tool for linguistic phylogenetics using BEAST 2

Abstract: We present a new open source software tool called BEASTling, designed to simplify the preparation of Bayesian phylogenetic analyses of linguistic data using the BEAST 2 platform. BEASTling transforms comparatively short and human-readable configuration files into the XML files used by BEAST to specify analyses. By taking advantage of Creative Commons-licensed data from the Glottolog language catalog, BEASTling allows the user to conveniently filter datasets using names for recognised language families, to impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…LingPy (cf. http://lingpy.org , accessed July 27, 2018), a suite of open source Python modules, provides state-of-the-art algorithms and visualizations for quantitative historical linguistics; BEASTLing 38 , a Python package, translates human-readable descriptions of phylogenetic inference into the complex driver files for the popular BEAST software; EDICTOR 39 , a graphical JavaScript application, allows scholars to edit etymological dictionary data in a machine- and human-readable way. While the development on these examples began before the CLDF standard, all three of them were originally using CSV dialects for easy data exchange and are now in the process of adding support for CLDF data, thus showing the value of interoperability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LingPy (cf. http://lingpy.org , accessed July 27, 2018), a suite of open source Python modules, provides state-of-the-art algorithms and visualizations for quantitative historical linguistics; BEASTLing 38 , a Python package, translates human-readable descriptions of phylogenetic inference into the complex driver files for the popular BEAST software; EDICTOR 39 , a graphical JavaScript application, allows scholars to edit etymological dictionary data in a machine- and human-readable way. While the development on these examples began before the CLDF standard, all three of them were originally using CSV dialects for easy data exchange and are now in the process of adding support for CLDF data, thus showing the value of interoperability.…”
Section: Resultsmentioning
confidence: 99%
“…http://glottobank.org/ ) being developed by a consortium of research centers and universities. Further, CLDF is by now already supported by a larger number of software packages and applications, ranging from libraries for automatic sequence comparison in historical linguistics (LingPy), via packages for phylogenetic analyses (BEASTLing 38 ), up to interfaces for data inspection and curation (EDICTOR 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is sure to give an exciting boost to research in the history and dispersal of languages, peoples and cultures. We will continue to use our own database in this context, improving the cognate annotation using tools like LingPy [ 41 ] and Edictor [ 55 ] and feeding into computational analyses using Beastling [ 68 ] and BEAST [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the vast number of possible extensions and model choices, BEAST2 configuration files tend to be unwieldy large and complex. In order to generate the configuration files for the analyses, we therefore use the Beastling application, version 1.4.0 (Maurits et al 2018(Maurits et al , 2017. Beastling allows the user to specify a phylogentic analysis for linguistics in a concise format, taking reasonable defaults for options not specified explicitly.…”
Section: Inference Procedures Using Mcmcmentioning
confidence: 99%
“…For example, there are now new methods for automatic cognate detection using state-of-the-art pairwise phonetic alignment algorithms (List 2012a,b, List & Greenhill & Tresoldi, et al 2018) that reach nearly 90% accuracy (B-Cubed F-score) in determining the cognate sets to be used in phylogenetic analyses . Bayesian phylogenetic inference research has empirically shown which models are useful for lexical data (Chang et al 2015, Kolipakam et al 2018) and many of these models have been made accessible (Maurits et al 2017) for easy use with linguistic data that is conforming to cross-linguistic standards (Forkel 2017. In addi- With this background it is natural to ask why linguists choose to rely on such ad-hoc methodology for determining linguistic subgroups.…”
Section: Introductionmentioning
confidence: 99%